2018
DOI: 10.1016/j.ijedudev.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with private-public school performance: Analysis of TALIS-PISA link data

Abstract: We use measures of competitive pressure, administrative autonomy and staffing practices to explain the private-public performance difference in Australia, Portugal and Spain using the TALIS-PISA dataset. We employ OLS regression and counterfactual decomposition analysis on matched sub-samples. These school factors do not explain the overall private-public performance gap in the three countries except at the higher-end of the distribution. In other words, these factors appear to benefit only the high-performers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
1
12
0
2
Order By: Relevance
“…Satisfaction with teaching is impacted by employment characteristics (i.e. private versus public school systems; Delprato & Chudgar, 2018). In particular, working conditions can impact the quality of teacher instruction and student achievement (Bettini et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Satisfaction with teaching is impacted by employment characteristics (i.e. private versus public school systems; Delprato & Chudgar, 2018). In particular, working conditions can impact the quality of teacher instruction and student achievement (Bettini et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The current study was not without limitations. Firstly, psychological distress can differ among teaching levels, for instance, between primary and secondary education (Eaton et al, 1990).Satisfaction with teaching is impacted by employment characteristics (i.e., private versus public school systems; Delprato & Chudgar, 2018). In particular, working conditions can impact the quality of teacher instruction and student achievement (Bettini et al, 2017).…”
Section: Methodological Considerations and Limitationsmentioning
confidence: 99%
“…Zhang, Khan, and Tahirsylaj (2015) have used regression methods to measure the factors affecting students' performance using the dataset of PISA 2009 participating countries. The research of Delprato and Chudgar (2018) has found out the systemic school factors on the privatepublic performance gap using the Teaching and Learning International Survey (TALIS)-PISA dataset in three countries. Based on a multilevel model, Giambona and Porcu (2018) have identified the most important factor on students' achievement was school size.…”
Section: Introductionmentioning
confidence: 99%
“…La décomposition par la distribution contrefactuelle est utilisée par Oliveira et al (2013) pour démontrer que les élèves peu performants fréquentant les écoles publiques obtiendraient de moins bons résultats avec les caractéristiques des élèves des écoles privées. Delprato et Chudgar (2018) démontrent qu'en Australie, Espagne et Portugal, les facteurs liés aux écoles (l'esprit de compétition, l'autonomie administrative, les pratiques d’équipe et la comptabilité) determinent le différentiel de performance entre écoles publiques et privées.…”
Section: Revue De La Litteratureunclassified